Penerapan Model Pembelajaran Kooperatif Scramble Untuk Meningkatkan Hasil Belajar Siswa Kelas V SD Negeri 1 Bukit - Ida Ayu Supadmi (Jayapangus Press, 2019)
This study aims to improve the learning outcomes of scramble type Cooperative Learning Models. This research is a classroom action research (CAR) which is designed through two cycles. The design of each cycle consists of the stages of planning, implementation, and evaluation. Each cycle is carried out in 3 times face to face in class and ends with a final cycle test. The subjects of this study were class VI students of 22 people, consisting of 10 male students and 12 female students. Data is collected through tests and observations. Based on the results of data analysis from each cycle and discussion that has been carried out, in the first cycle to the second cycle shows that the application of scramble type cooperative learning models can improve learning outcomes of Hinduism Education in fifth grade students of 1 Hill Elementary School in the academic year 2017/2018 even semester and an increase in the learning outcomes of Hindu Education in each cycle. The increase occurred in the classical mean from 74.32 to 84.55 and learning completeness from 77.27% to 90.91%.